PENGEMBANGAN MEDIA FLIPBOOK INTERAKTIF MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK SMA KELAS X - Ainin Mahirrita Nisa; Reni Ambarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
21st-century education is characterized by the development of digital technology that demands innovation in learning. One important factor in successful learning is student motivation. However, learning motivation is still relatively low, especially for the broad and complex material of biodiversity. Data from the Education and Culture Center (Puspendik) shows that the average score of the 2019 National Biology Examination was 50.61 and is still considered low. Therefore, this study aims to develop an interactive flipbook media for biodiversity material to increase the learning motivation of grade 10 high school students. This study uses the 4D development model (Define, Design, Development, Disseminate). The instruments used include expert validation sheets, readability tests using fry charts, teacher and student responses, observations of learning implementation, and a questionnaire of student responses to learning motivation. The results of the flipbook development research obtained a validity of 3.75 (very valid), the practicality of the flipbook was in the very practical category with the results of the level 10 readability test, 100% teacher response, 98.5% student response, 97.95% implementation observation, and the effectiveness of the flipbook was seen from the achievement of learning motivation indicators which obtained a score of 95.62% (very effective). Thus, the interactive flipbook media for biodiversity material was declared valid, practical, and effective in increasing the learning motivation of grade X high school students.